Pengaruh Penggunaan E-Modul Prakonsepsi Terhadap Perilaku Persiapan Kehamilan Sehat Pada Wanita Usia Subur Di Kabupaten Wonosobo Tahun 2022 - Isti Hartini (LPPM STIKES Guna Bangsa, 2022)
ABSTRACT Background: Maternal and infant mortality rates are still high in Wonosobo Regency. This mortality rate can be prevented by preparing for a healthy pregnancy and delivery through preconception care. In order for women of childbearing age to carry out preconception care, it is necessary to provide preconception education. Research Objectives: To determine the effect of the preconception e-module on the behavior of preparing for a healthy pregnancy in women of childbearing age. Research Methods: Experiment with pretest–posttest with control group, carried out from January to April 2022. The population was 967 women of childbearing age, a sample of 96 people was taken by random sampling that met the inclusion and exclusion criteria. Data analysis used paired t-test, z test and MANCOVA. The measuring instrument uses a questionnaire. Results and Discussion: There is a difference in the increase in knowledge between the two groups with p-value = 0.00, there is a difference in the increase in attitude between the two groups with p-value = 0.00, there is a difference in the increase in behavior between the two groups with p-value = 0.00. Conclusion: There is an effect of using preconception e-module on healthy pregnancy preparation behavior in women of childbearing age. Research needs to be done to increase the knowledge of women of childbearing age about preconception with various media that attract people's learning interest. Keywords: Behavior, E-Module, Pregnancy Preparation